2018
DOI: 10.1021/acs.biochem.8b00022
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Origins of Enzyme Activation in Human Glucokinase Variants Associated with Congenital Hyperinsulinism

Abstract: Human glucokinase (GCK) acts as the body’s primary glucose sensor and plays a critical role in glucose homeostatic maintenance. Gain-of-function mutations in gck produce hyperactive enzyme variants that cause congenital hyperinsulinism. Prior biochemical and biophysical studies suggest that activated disease variants can be segregated into two mechanistically distinct classes, termed α-type and β-type. Steady-state viscosity variation studies indicate that the kcat values of wild-type GCK and an α-type variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
(101 reference statements)
0
11
0
Order By: Relevance
“…Our in vitro studies also showed increased enzyme activities for both mutants, and increased thermal stability for the M197V mutant. A recent report suggests two mechanisms of GCK activation among the gain‐of‐function mutations: α‐type activation results from a shift in the conformational ensemble of unliganded GCK toward a state resembling the glucose‐bound conformation, whereas β‐type activation is attributable to an accelerated rate of production release. It was reported that V91 was located in the allosteric activator region, and as a close neighbor, K90R is likely to be directly activated by structural changes and appears to be α‐type.…”
Section: Discussionmentioning
confidence: 99%
“…Our in vitro studies also showed increased enzyme activities for both mutants, and increased thermal stability for the M197V mutant. A recent report suggests two mechanisms of GCK activation among the gain‐of‐function mutations: α‐type activation results from a shift in the conformational ensemble of unliganded GCK toward a state resembling the glucose‐bound conformation, whereas β‐type activation is attributable to an accelerated rate of production release. It was reported that V91 was located in the allosteric activator region, and as a close neighbor, K90R is likely to be directly activated by structural changes and appears to be α‐type.…”
Section: Discussionmentioning
confidence: 99%
“…[79] While the mechanism of action is not known, BAD BH3 domains might stabilize specific conformations of GCK or accelerate product release, which has been observed in some activating GCK mutations. [40] This new interaction site could be exploited for future drug development. In fact, stabilized BAD BH3 domain helices have already shown promising therapeutic utility as they restore proper β-cell function and insulin secretion in BAD-deficient β-cells.…”
Section: Formation Of a Heteropentameric Complex At The Mitochondrialmentioning
confidence: 99%
“…We recently reported that activating mutations in GCK can result in global conformational alterations. [38,40] It is possible that SUMOylation also alters the conformational dynamics of GCK, as has been observed for other proteins [107,[118][119][120][121], but an investigation into the structural consequences of GCK SUMOylation has yet to be pursued. In particular, it remains to be determined which enzyme conformations of GCK are amenable to SUMOylation.…”
Section: Conjugation Of the Small Ubiquitin-like Modifier Protein (Sumentioning
confidence: 99%
See 2 more Smart Citations